Fully Automated Quantification of the Striatal Uptake Ratio of [99mTc]-TRODAT with SPECT Imaging: Evaluation of the Diagnostic Performance in Parkinson's Disease and the Temporal Regression of Striatal Tracer Uptake. (20th August 2015) - Fang, Yu-Hua Dean; Chiu, Shao-Chieh; Lu, Chin-Song; Yen, Tzu-Chen; Weng, Yi-Hsin
Abstract : Purpose . We aimed at improving the existing methods for the fully automatic quantification of striatal uptake of [T c 99 m ]-TRODAT with SPECT imaging. Procedures . A normal [T c 99 m ]-TRODAT template was first formed based on 28 healthy controls. Images from PD patients (n = 365 ) and nPD subjects (28 healthy controls and 33 essential tremor patients) were spatially normalized to the normal template. We performed an inverse transform on the predefined striatal and reference volumes of interest (VOIs) and applied the transformed VOIs to the original image data to calculate the striatal-to-reference ratio (SRR). The diagnostic performance of the SRR was determined through receiver operating characteristic (ROC) analysis. Results . The SRR measured with our new and automatic method demonstrated excellent diagnostic performance with 92% sensitivity, 90% specificity, 92% accuracy, and an area under the curve (AUC) of 0.94. For the evaluation of the mean SRR and the clinical duration, a quadratic function fit the data withR 2 = 0.84 . Conclusions . We developed and validated a fully automatic method for the quantification of the SRR in a large study sample. This method has an excellent diagnostic performance and exhibits a strong correlation between the mean SRR and the clinical duration in PD patients.